Preparasi, Karakterisasi dan Evaluasi Pelepasan Obat dari Beads Kalsium Alginat Deksametason dengan Metode Gelasi Ionik - Aulia, Christye; Djajadisastra, Joshita (Majalah Ilmu Kefarmasian, 2012)
Inflammatory Bowel Disease (IBD) is a disease of inflammation in the colon. Targeted delivery systems for the treatment of IBD is designed to increase the drug concentration in the local tissue. Dexamethasone is a drug having anti-inflammatory and antifibrosis effects which is used to repair scar tissue arising from postoperative IBD. This research purpose to create calciumalginate beads dexamethasone to be released only in the colon. Beads were made by using sodium-alginate and Ca2+ as crosslinker by ionic gelation method, with ratio between sodium alginate-dexamethasone (3:1). A concentration of solution sodium alginate 3 % b/v with variation concentration of crosslinker is 2% (formula 1), 3% (formula 2), and 4% (formula 3). Beads were characterized and drug release determined. The results obtained were spherical beads with a size range between 630 > 800 µm with the greatest encapsulation efficiency obtained from the beads formula 1 with the amount of 98.14% and after coated with Eudragif ® S100 using a fluid bed dryer apparatus, beads of formula 4 was obtained with an encapsulation efficiency of 67, 78%. Beads formula 1 were only released in stomach pH and not able to hold up the release of the active substance in colonic pH, whereas beads of formula 4 releasing dexamethason gradually more than 8 hours in colonic pH, and has a better release profile for the active substance.